Pengelolaan Bantuan Keuangan Partai Politik terhadap Anggaran Pendidikan Politik di DPD Partai Keadilan Sejahtera (PKS) Kota Makassar - Baso Sardjan; Adriani Adriani; Muh. Sofian Assaury Yahya (YUME : Journal of Management, 2022)
Abstract :The formulation of the problem in this study is to describe the indicators of accountability for financial management of the PKS party DPD Makassar (legal certainty, program planning/policy, program implementation and accountability). The data used in this study came from the results of interviews by PKS DPD officials and the results of field observations using Miles and Hubberman analysis techniques.the results of research in the management of financial assistance of the Makassar City PKS DPD in this research are measured from the aspect of legal certainty that the Makassar City PKS DPD has followed the elements that have been determined by the government. This is in accordance with Government Regulation Number 83 of 2012 Article 1 Paragraph (2), that the financial assistance provided is in accordance with the number of valid votes obtained by the Makassar City PKS DPD. The arrangement in the budget for political education is also in accordance with the applicable provisions, namely by prioritizing its use for political education by 60%. In the aspect of planning/policy, the choice made by party administrators is categorized as quite good because in the process the Makassar City PKS DPD prepares policies that still consider the adequacy of existing funds. However, in its implementation, there are often discrepancies / discrepancies between political parties and the understanding of the general public. while the aspect of accountability Referring to the data from interviews, DPD PKS has experienced problems in the proof of expenditure on the funds used, namely the honorarium note. In the interview, the informant reasoned that this happened because the activity invited internal speakers/board members, so the management felt reluctant/uneasy. Things like this should be the concern of Kesbang/BPK in conducting inspections, so that there is no misuse of the funds provided.Â Keywords : Accountability, party financial assistance